The Birth of Star Clusters (Astrophysics and Space Science Library,, 2018)
All stars are born in groups. The origin of these groups has long been a key question in astronomy, one that interests researchers in star formation, the interstellar medium, and cosmology. This volume summarizes current progress in the field, and includes contributions from both theorists and observers. Star clusters appear with a wide range of properties, and are born in a variety of physical conditions. Yet the key question remains: How do diffuse clouds of gas condense into the collections of luminous objects we call stars? This book will benefit graduate students, newcomers to the field, and also experienced scientists seeking a convenient reference.